ijee 2022
DOI: 10.48165/ijee.2022.58240
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of Access to Credit and Availing Subsidies for Protected Cultivation in Maharashtra

Abstract: Protected cultivation requires high initial investment and intensive use of inputs for crop production but offers better yield which in turn increases the profitability of the farm. The study attempts to explore the economics of protected cultivation with different interest rates regime and subsidy in Pune and Nasik districts of Maharashtra conducted during 2018-19. About 95 to 97 per cent of the farmers availed subsidy from the government and the rest of the farmers constructed their polyhouse and shade net h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Mehta et al, (2016) in their study on Indian Kisan Credit Card Scheme found similar results about compound growth rates in their study during 2004-14. Prakash et al, (2022) also found similar results.…”
Section: Progress Of Kcc Scheme With Respect To Number Of Cards Issue...supporting
confidence: 68%
“…Mehta et al, (2016) in their study on Indian Kisan Credit Card Scheme found similar results about compound growth rates in their study during 2004-14. Prakash et al, (2022) also found similar results.…”
Section: Progress Of Kcc Scheme With Respect To Number Of Cards Issue...supporting
confidence: 68%
“…Thus the problem of overdue could be minimized provided the utilization of loans is supervised effectively and the farmers are approached at the right time for repayment. The bank should take responsibility for supplying the loans according to farmers' needs and at the beginning of the crop season to improve the chances of recovery (Prakash et al, 2022). Competent management is also required to organize the recovery drive more efficiently.…”
Section: Extent Of Repayment Of Crop and Allied Agricultural Loan By ...mentioning
confidence: 99%